Myoconjunctival Enucleation Study (MES): Outcome of Myoconjunctival Enucleation Technique with Polymethyl Methacrylate (PMMA) implant and Custom-made prosthesis (CMP) in a tertiary eye care center in Nepal - Hom Bahadur Gurung; Purnima Rajkarnikar Sthapit; Malita Amatya; Dikshya Bista; Sushant Adiga; Manish Poudel; Raba Thapa; Rohit Saiju (PLoS ONE, 2025)
Purpose To evaluate the average motility of the implant and custom-made prosthesis (CMP) in various gazes following Myoconjunctival enucleation, the surgical duration, and the complications encountered at a tertiary eye hospital. Methods This was a prospective, non-randomized interventional study. Recti muscles were sutured to the fornices before enucleation of the eyeball to minimize surgical time and the need for additional sutures. Thirty-five consecutive patients meeting the inclusion criteria were enrolled. Data on surgery time, complications, and implant/prosthesis motility were recorded and analyzed. Results The mean surgical duration was 39.43 ± 4.97 minutes. Mean PMMA implant movement was 2.34 mm in elevation, 2.26 mm in depression, 2.74 mm in abduction, and 2.71 mm in adduction. Custom-made prosthesis (CMP) movement was 2.40 mm in elevation, 2.51 mm in depression, 2.74 mm in abduction, and 2.66 mm in adduction. Complications were minimal: one intraoperative superior rectus slippage, a few cases with early postoperative nausea, vomiting, and headache, all resolved within a week. At six weeks, one suture granuloma and one shallow inferior fornix were noted and managed. Patient satisfaction was high (88.57%), with a mean Likert score of 4.25 ± 0.65 (1 = Very unsatisfied to 5 = Very satisfied). No patient reported dissatisfaction. Conclusion Myoconjunctival enucleation offers favorable implant and prosthesis motility, a relatively short surgical duration, and minimal complications. High patient satisfaction supports the myoconjunctival enucleation technique as a reliable and well-tolerated surgical option.